Réseau d'entreprises autochtones : analyse des facteurs du capital social pour la réussite d'une initiative dans le secteur forestier québécois - Serban, Luca Gabriel (Université Laval, 2020)
Indigenous entrepreneurship, in Canada and around the world, has received growing attention for its potential to reduce poverty and social marginalization. Thus, the capacity of an Indigenous community to create wealth depends, in part, on its ability to 'opt in' to the economy and establish business relationships. An Indigenous business network seeks to generate knowledge and opportunities on the market, as well as bring mutual benefits at the business level and socioeconomic benefits at the community level. While business network benefits have been documented in the literature few empirical research explore this concept in the context of indigenous communities. The purpose of this research is to better understand needs, challenges and opportunities related to business network in an Indigenous context. We used an exploratory approach and we worked collaboratively with the First Nations of Quebec Forestry Network (FNQFN). Semi-structured interviews were conducted with Indigenous forest company representatives. This research shows that the needs expressed for a network of Indigenous business corresponds to several elements identified in the literature. These include easier access to information, sharing of expertise, contributions to collective well-being, greater political influence, and opportunities to develop new markets. Additionally, our results highlight several challenges to the establishment of an indigenous business network: funding, trust, distance between members, and political support at the national and local level. This research contribute to a better understanding of the conditions that enhance the success of indigenous enterprises. For political leaders, it can guide the development of more effective solutions to meet the needs of Indigenous economic development and the creation of wealth at the local level. L’entrepreneuriat autochtone, au Canada et dans le monde, a fait l’objet d’une attention croissante pour son potentiel de réduction de la pauvreté et de la marginalisation sociale. Ainsi, ...